APPLICATION OF SINGLE MOVING AVERAGE METHOD TO PREDICATE TEMPE SALES IN HOME INDUSTRY GEDANGAN VILLAGE - Eva Tri Wahyuni; Mohd. Siddik; Masitah Handayani (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
The home industry of making tempe is one of the businesses engaged in the sale of tempe products. Activities in the industry include the production of tempe sales and purchase transactions. The problem that occurs in the industry is to determine each production of the amount of tempe sales which often have difficulty in determining how much to sell for the next period. This results in frequent shortages of stock or even a large amount of tempe sales stock remaining so that it cannot meet customer needs and buildup in warehouses for a long period of time. The purpose of this study was to predict sales of tempe in the home industry of Gedangan Village to meet consumer needs. The method used in this study is the Single Moving Average (SMA) method, which is a forecasting method carried out by taking observations from the past, then looking for the average value as a forecast for the coming month. The results of the application of the Single Moving Average method produce predictions of tempe sales in January 2022 as many as 9106.67 sold with an accuracy of 5% MAPE error and the system created can facilitate the prediction of tempe sales quickly and accurately. So it can be concluded that the Single Moving Average method can help predict sales of tempe in the following month.